Systematic Literature Review : Models and Indicators for MSME Performance Measurement - Dyah Arini R; Sudarmiatin Sudarmiatin; Agus Hermawan (Global Management: International Journal of Management Science and Entrepreneurship, 2025)
This study employs the Systematic Literature Review (SLR) method following the PRISMA 2020 Statement guidelines to identify the main models and indicators used in measuring the performance of Micro, Small, and Medium Enterprises (MSMEs). The literature selection process includes the stages of identification, screening, eligibility assessment, and inclusion, resulting in ten articles from reputable Q1 international journals. The analysis reveals that the most frequently used performance measurement models are integrated performance models such as the Balanced Scorecard, Performance Prism, and models based on resource capability, customer, internal process, and financial perspectives. Commonly used indicators include sales growth, profitability, market share, customer satisfaction, process flexibility, technology adoption, and business sustainability. The study concludes that although financial measures remain dominant, non-financial dimensions—such as digital capability, stakeholder engagement, and internal process effectiveness—are increasingly important for MSMEs operating in the context of global market dynamics and digital transformation. The implications of this study provide theoretical contributions to the development of MSME performance measurement frameworks and offer practical guidance for MSME managers in selecting indicators that align with the characteristics of small and medium-sized enterprises.